Crinoidea and Asteroidea (Echinodermata) from the slope of the Yucatan Peninsula, Colección Nacional de Equinodermos, Mexico - Durán-González, Alicia; Laguarda-Figueras, Alfredo; Solís-Marín, Francisco A.; Gracia, Adolfo (Revista de Biología Tropical, 2024)
Introduction: The species of the Crinoidea and Asteroidea classes are distributed in a wide variety of habitats in all oceans from the intertidal zone to great depths, there are few Mexican records in depths greater than 200 m, the few existing records date from historical documents in the specialized literature and the specimens are kept in foreign scientific collections. Objective: Contribute to the collection of information on the specimens kept in the Colección Nacional de Equinodermos (CNE) of Instituto de Ciencias del Mar y Limnología (ICML), UNAM and provide an inventory of the species of crinoids and asteroids that inhabit deep areas of the slope of the Yucatan Peninsula, Mexico. Methods: From 2005 to 2014, specimens of crinoids and asterioids were collected through four cruises in the B/O “Justo Sierra” BIOREPES 1 and 2 and COBERPES 2 and 6, shrimp net trawls were carried out at 80 sampling stations. Results: The taxonomic list includes 1146 specimens, of which 204 crinoids are of the order Comatulida, distributed in three families, three genera and three species and 942 asteroids distributed in six orders, 11 families, 21 genera and 28 species. New records were obtained for CNE: Democrinus rawsonii and Atelecrinus balanoides in crinoids. Astropecten alligator, Hymenaster modestus, Calyptraster personatus, Pteraster militarioides militarioides, Sclerasterias contorta in asteroids. With this information, the records of crinoids and asteroids (deeper than 200 m) increase for the states of Yucatan (16) and Quintana Roo (16).